Sports, culture and society: Why the Netherlands are successful in elite sports and Belgium is not? A comparison of elite sport policies - de Bosscher, V.; de Knop, P.; van Bottenburg, M. (Kinesiologia Slovenica, 2008)
This paper reports the findings of a comparative study on elite sport policies in Flanders and the Netherlands. The aim is to find out whether differences in elite sport policies can explain the under-performances during international competitions of Flanders compared to the Netherlands. A nine pillar model of sports policy factors leading to international success was operationalised through several critical success factors. One of the key elements is the involvement of the athletes, coaches and performance directors in the data collection, in order to have a standardised measure of hypothetical concepts that cannot be observed directly and to assess the elite sport climate as it is perceived. The results showed remarkable differences in the organisation and long-term planning of elite sport policies, financial support for elite sport purposes, a holistic approach towards athletic development, coach development opportunities and the dissemination of scientific information. It was concluded that policy differences may explain differences in success in the two nations to a large extent, but extraneous influences are inherent to international comparative studies and make it therefore impossible to create a theory that is totally construct valid.